Formic Acid Synthesis via Biomimetic Autoxidation of Carbon Dioxide and Methane (Biogas and Flare Gas) in Low-Temperature for Carbon Capture and Hydrogen Fuel Carrier Applications - Nugroho, Rio; Purwadi, Ronny; Aqsha; Soerawidjaja , Tatang Hernas; Sasongko , Setyo Yanus (ASEAN Journal of Chemical Engineering, 2025)
The transition from fossil fuels to renewable energy sources and the utilization of CO₂ through CCU are crucial steps toward energy sustainability. Biogas, a renewable energy source primarily composed of CH4 and CO2, holds significant potential in this context. On the other hand, gas flaring continues to contribute to greenhouse gas emissions, yet it also presents an opportunity for utilization. Another challenge in utilizing gaseous fuels lies in their storage and transportation over long distances. This study aims to develop a liquid-phase autoxidation for CH4 and CO₂ to produce formic acid using synthetic catalysts that mimic the function of the MMO enzyme. Formic acid can act as a future fuel solution due to its role as a liquid hydrogen carrier. In this exploratory study, four types of catalysts based on iron and copper were synthesized. These catalysts were tested in the autoxidation reaction of CH4 and CO₂ in an ethanol solution at 65°C, followed by condensation at 20°C to obtain a distillate as the product. The results of this study indicate that the Cu,Fe-acetate catalyst exhibits the highest catalytic activity, achieving 6.81 mol HCOOH/kg catalyst·hour with a methane conversion to formic acid of 8.61%. Adding Cu to the Fe-Acetate catalyst increased its catalytic activity by 29.76%. Conversely, adding Cu to Fe-Format decreased catalytic activity by 36.54%.